Perancangan Sistem Informasi Hasil Produksi Sawit pada PT. Torganda Berbasis Web - Butarbutar, Cecilia Margareta; Parangin-angin, Resianta; Saragih, Rijois Iboy Edwin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The palm oil industry is one of the strategic sectors in the Indonesian economy, but the management of its production data still faces several obstacles, especially in recording and reporting processes that are still carried out manually. This study aims to design and develop a web-based palm oil production information system at PT. Torganda to improve efficiency, accuracy, and data processing speed. The research methods used include observation, documentation, and system analysis. The system was designed using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and a structured database design. The results show that the system can automate harvest data processing, accelerate the creation of daily, monthly, and annual reports, and provide real-time information access. Thus, the system has the potential to improve operational performance and support timely decision-making at PT. Torganda.